ANALISIS TINGKAT LIKUIDITAS PADA PT. TELEKOMUNIKASI INDONESIA Tbk - SEFLIN SINTIA KURANTA; JHONNY MONTOLALU; DOLINA L. TAMPI (JURNAL ADMINISTRASI BISNIS, 2016)
ABSTRACT : The purpose of this study was to analyze the level of liquidity PT. Telekomunikasi Indonesia Tbk. If the company has good liquidity, the company was able to survive and complete with other companies. The method used in this research is descriptive quantitative method using liquidity ratio to Analyze the level of liquidity of the company. Based on the results of the analysis carried out showed that the level of liquidity PT. Telekomunikasi Indonesia Tbk has a Current Ratio percentage value of 113.98% in the years 2011- 2015. Quick Ratio values in the years 2011-2015 have a percentage of the value of 107.8%. Cash Ratio values in the years 2011-2015 have a value percentage of 57.9%. PT. Telekomunikasi Indonesia Tbk have good liquidity in the years 2011- 2015. Telekomunikasi Indonesia Tbk have a favorable cash criteria from the perspective of anyone because it is not too high and not too low.Company’s liquidity is maintained and cultivated for the future could continue to affort to meet the level of liquidity with a good percentage. Keywords : Liquidity, Current Ratio, Quick Ratio, Cash Ratio.